Kelp forest: enhancing biodiversity and mitigating climate change - Camilla Brendon (Applied Phycology)
‘Kelp Forest – Enhancing Biodiversity and Mitigating Climate Change’ explores the use of contemporary art to promote climate awareness and action. The project aims to make ocean exploration accessible to urban communities, particularly those without direct access to diving experiences. It encompasses an immersive art installation, ‘Kelp and Critters’ creative workshop, and a panel discussion ‘What Kelp Does for Us’. The installation, constructed entirely from found and recycled materials, including debris collected from inland and coastal water systems and donations from The Port of London Authority, creates a striking sensory experience. Some versions incorporate living plants, visually demonstrating the parallels between kelp forests and terrestrial forests in oxygen production and carbon sequestration. The work invites audiences to engage with an underwater environment by walking among enormous sculptures of plastic algae. This project underscores the ecological significance of kelp forests as critical marine habitats that store carbon, provide food and shelter, produce oxygen, and protect coastlines. By linking art, science, and community engagement, it fosters public understanding of how kelp forests mitigate climate change and support biodiversity.